Prevalence of Helicobacter pylori Infection Detected by ELISA in Blood and Stool Samples: A Cross-Sectional Study in Al-Bayda, Libya (2024–2025) (Comprehensive Journal of Science, 2025)
Background and Aim: Helicobacter pylori infection represents a major global healthchallenge, with epidemiological patterns showing considerable geographic variation. Thisinvestigation sought to evaluate the current status of H. pylori infection within a patientpopulation in Al-Bayda, Libya, focusing on infection frequency and its correlation with keydemographic variables.Methods: This observational analysis was carried out between 2024 and 2025. The studycohort comprised 748 individuals. Detection of H. pylori was performed using enzyme-linkedimmunosorbent assay (ELISA) techniques on two sample types: serum for quantifyingspecific IgG antibodies and stool for identifying bacterial antigens.Results: Laboratory analysis identified a positive infection rate of 39.3%. The data revealed ahigher frequency of positive results among female participants (64.6%) compared to male
Keywords: Helicobacter pylori, Epidemiology, Seroprevalence, Libya, Diagnostic Methods, Stool Antigen Test, IgG Antibodies.